Increasing the Capacity of KWT Barokah Through Agricultural Cultivation Innovation in Banjardowo Village, Semarang - Sholeh, Muh.; Indardi, Nanang; Anwar, Khoirul; Gumala, Vacktian Diva (Jurnal Abdimas, 2025)
The coastal city of Semarang faces serious challenges in the form of limited land and the threat of flooding, which reduce agricultural productivity. These conditions have prompted the implementation of urban farming-based cultivation innovations as an adaptation strategy. This community service research aims to increase the capacity of the Barokah Women Farmers Group (KWT) in Banjardowo Village. The activities were carried out participatively through six main stages, namely socialisation, construction of urban farming installations, training in planting media production, training in seedling planting, mentoring, and evaluation. The results of the activities showed an increase in the knowledge and skills of members in horticultural cultivation relevant to limited urban land. In addition, these activities strengthened the social cohesion of the group through a spirit of mutual cooperation and collaboration. The urban farming programme at KWT Barokah has proven effective in enhancing technical capacity, empowering women, and strengthening local food security. This programme also supports the achievement of the Sustainable Development Goals (SDGs), particularly points 2, 11, and 12.